Serum pepsinogen levels indicate the requirement of upper gastrointestinal endoscopy among Group A subjects of ABC classification: a multicenter study. - Chinda, Daisuke; Shimoyama, Tadashi; Mikami, Tatsuya; Arai, Tetsu; Chiba, Daisuke; Sasaki, Yoshio; Komai, Kazuo; Sawada, Yoshihiko; Saito, Yoshiharu; Chiba, Hironobu; Fukuda, Shinsaku; RINGO Study Group (Journal of Gastroenterology, 2018)
Background: ABC classification has been used to assess the risk for gastric cancer. The current problem of ABC classification is that Group A contains individuals with current and past H. pylori infection. The aims of this study were to assesse the proportion of current and past infection in Group A and to establish a criteria for the identification of subjects with past infection from Group A subjects with negative results of urea breath test (UBT) and/or stool antigen test.Methods: 201 subjects classified into Group A received UBT and/or stool antigen test, and also subsequent upper gastrointestinal endoscopy. The subjects were classified by the status of H. pylori infection defined by endoscopic findings. Levels of pepsinogen (PG) I, PG II and PG I/II ratio were compared between the groups, and receiver operating characteristic curves were constructed to extract the corresponding cutoff values.Results: 22 subjects were tested positive by UBT and/or stool antigen test. Endoscopic images of 157 out of 179 subjects were studied. 15 of the subjects were regarded to have past H. pylori infection. The optimal cut-off value of PG I and PG I/II ratio for the determination of past H. pylori infection were ≤ 31.2 ng/mL and ≤ 4.6, respectively.Conclusions: Approximately 20% of Group A subjects have current or past H. pylori infection. Addition of UBT and/or stool antigen test can identify current but not past infection. Serum PG levels would be useful to identify subjects with past H. pylori infection.